2021
DOI: 10.3390/f12050527
|View full text |Cite
|
Sign up to set email alerts
|

Fibers Obtained from Invasive Alien Plant Species as a Base Material for Paper Production

Abstract: Invasive alien plant species (IAPS) are one of the biggest challenges in European ecosystems, displacing local vegetation, destroying agricultural land, and causing billions of dollars of damage to the European economy every year. Many of them are removed daily and mainly burned. In this work, we investigated the possibilities of using plants as feedstock for paper production. Papers made from three invasive alien plants, i.e., Knotweed, Goldenrod, and Black locust, were studied and compared with commercial of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…60 In other words, it gives information on how well a material absorbs energy. 60 Marica et al 61 reported a similar trend of tan d for cellulosic papers from different plants, reporting that the viscoelastic behavior of cellulosic papers can be mainly attributed to the lignin and hemicellulose. 61 It is also important to emphasize that the temperature relaxation behavior of the cellulose structure is extremely complex due to its heterogeneity, so it is difficult to distinguish which component is responsible for the overall behavior of the structure.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 79%
“…60 In other words, it gives information on how well a material absorbs energy. 60 Marica et al 61 reported a similar trend of tan d for cellulosic papers from different plants, reporting that the viscoelastic behavior of cellulosic papers can be mainly attributed to the lignin and hemicellulose. 61 It is also important to emphasize that the temperature relaxation behavior of the cellulose structure is extremely complex due to its heterogeneity, so it is difficult to distinguish which component is responsible for the overall behavior of the structure.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 79%
“…Although there are some detrimental effects on the ecology, economy, and human health of such species, they are exploited as animal feed, food source, ornamental, and traditional medicine (Feng et al 2021). Because of their abundant biomass, several exotic species have exhibited added values for paper production (Starešinič et al 2021) and cosmetics (Nguyen et al 2021d).…”
Section: Perspectivementioning
confidence: 99%
“…It was obtained from Goldenrods, Knotweeds and Black Locust papers with a quality suitable for their sale and even for printing (Starešinič et al, 2021. Natural dyes such as the one produced from the petals of Impatiens glandulifera can be used in obtaining colored paper (Klančnik, 2021).…”
Section: Fiber Production and Their Usementioning
confidence: 99%
“…Invasive species causes serious economic problems (Adelino et al, 2021, Shahrtash and Brown, 2021, Starešinič et al, 2021 and imbalances in the ecosystems where these settle in (Starešinič et al, 2021), even in protected areas (Pathak et al, 2021, Bakacsy andBagi, 2020) where a low number of classical control methods can be implemented (Ngondya et al, 2019). Unfortunately, most of the time interest is given to covering losses incurred, not to preventing them (Adelino et al, 2021).…”
Section: Introductionmentioning
confidence: 99%